A Comprehensive Review on the Mechanism, Risk Factors, and Management of Muscle Cramping - Chen, Junhe (Exploring Science Academic Conference Series, 2026)
Muscle cramps are sudden, involuntary, and painful spasms of skeletal muscles. This condition affects 37% of the general population each year. It is a common complaint in practice. Muscle cramps occur suddenly and can last for a few seconds to a few minute s. They can be associated with exercise or rest, or can be a manifestation of a medical condition. There is controversy regarding the pathophysiology of muscle cramps. Two theories have been advanced in the literature to explain muscle cramps. They include the dehydration/electrolyte imbalance hypothesis a nd the altered neuromuscular control hypothesis. This paper provides a comprehensive overview of the current literature on the pathophysiology, risk factors, and management of muscle cramps. The literature suggests that exercise -associated muscle cramps (E AMCs) result from a variety of factors. It is suggested that muscle cramps result from a combination of intrinsic and extrinsic factors. One such factor is neuromuscular fatigue. Passive stretching is the mainstay in the management of muscle cramps. Simila rly, prevention is also individualized according to the risk factors. Pharmacological agents such as methocarbamol, orphan Adrien, and taurine are effective in patients with cirrhosis.